SISTEM INFORMASI GEOGRAFIS PARIWISATA KULINER DI SEMARANG BERBASIS WEB - ARDIE SEPTIA ANGGORO, 10.01.55.0043 (Information Technology and Telematics, 2017)
Abstract             Culinary tourism is now becoming one of a kind travel very large impact on the development of an area. One area of importance is to cultivate the promotion of native food potential areas that could be appointed as a culinary known in foreign countries. In this study developed a web-based application that is able to manage and display information culinary tourism in the city of Semarang. Information comes with dynamic maps. This application is expected to overcome some of the limitations of the map manually. Map used to use the features of Google Map which is an online map application service provided by Google.  System development method used in this study, namely Web GIS Development Life Cycle. Design using UML, system implementation using PHP and MySQL.  The results of this research are system geographic information culinary tourism in the city of Semarang can display information culinary tourism in the form of marker map google map and detailed information culinary consisting of photo culinary tourism, the name of culinary tourism, detail culinary, address and sub culinary tourism. KeywordsSIG, Google Map, WisataKuliner, Semarang